The notification of the claim as a guarantee of the right to defense and due process (GnosisWisdom, 2023)
The general objective of the study is to determine the effects of the application of article 157 of the Civil Procedure Code in the Justices of the Peace Lawyer of the Superior Court of Justice of Puno - Period 2019. Regarding the methodology, the study is of a quantitative paradigm of a functional sociological method; It is important to mention that the study is of a descriptive level, of a basic type, of an explanatory level, of a non-experimental-correlational design and of transversal temporality. Regarding the population, it consists of trial lawyers, judicial assistants and judges to whom a questionnaire with 31 items was applied. Results: 75% of the respondents affirm that the application of electronic notification in the Justices of the Peace Lawyer has positive effects. Conclusions: The existence of positive effects of the application of article 157 of the Civil Procedure Code in the Justices of the Peace is specified; this since the respondents affirmed that it has and will have positive effects in the Justices of the Peace, since the users manage to have knowledge of the objective of the notification; In addition to the fact that the electronic medium allows to have advantages such as: confidentiality, security and accessibility; and added to this, the judges and judicial assistants confirm that there is better notification in the different resolutions issued by the Justices of the Peace.
Keywords: Procedural acts; administration of justice; electronic notification; procedural speed; procedural burden; procedural economy